Diurnal and seasonal variations in photosynthetic rates of dwarf pine Pinus pumila at the treeline in central Japan - Ryuto Shimada; Koichi Takahashi (Arctic, Antarctic, and Alpine Research, 2022)
It is important to develop a convenient method for predicting photosynthetic rates in cold regions such as high elevations. Dwarf pine Pinus pumila is a representative treeline species in Japan. In this study, we investigated how environmental factors affect diurnal and seasonal variations of the in situ photosynthetic rate of P. pumila. Five environmental factors (photosynthetic photon flux density [PPFD], air temperature [Ta], soil temperature [Ts], vapor pressure deficit [VPD], and soil water content [SWC]) were examined. Photosynthetic measurements were conducted for four needle ages at hourly intervals on fifteen days from July to October 2018. The net photosynthetic rate decreased with needle age and changed seasonally and diurnally for each needle age. The net photosynthetic rate showed unimodal patterns with Ta, Ts, and SWC. The seasonal and diurnal changes in the net photosynthetic rate were related to seasonal changes in the four environmental factors (PPFD, Ta, Ts, SWC); the net photosynthetic rate decreased in mid-summer when Ta, Ts, and PPFD were high due to a decrease in SWC. Seasonal and diurnal changes in net photosynthetic rates could be reproduced by the multiplicative model of the four environmental factors and needle age. Therefore, the photosynthetic rate of P. pumila can be explained and predicted using these environmental factors and needle age. This information will be useful for predicting the effects of climate change on the photosynthetic production of plants in cold regions.